2006
DOI: 10.1590/s0074-02762006000200001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological pattern and mortality rates for hepatitis A in Brazil, 1980-2002: a review

Abstract: The prevalence of hepatitis A virus (HAV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 39 publications
2
31
1
4
Order By: Relevance
“…In Brazil, seroprevalence studies conducted recently mainly in urban areas, showed a consistent decrease of the incidence rates in childhood 4,5,6,7,8,9,10 . Decrease in HAV circulation 8,9,11,12 as well as a progressive decline in fatal cases related to HAV infection in all Brazilian regions 8 have also begun to be noticed.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…In Brazil, seroprevalence studies conducted recently mainly in urban areas, showed a consistent decrease of the incidence rates in childhood 4,5,6,7,8,9,10 . Decrease in HAV circulation 8,9,11,12 as well as a progressive decline in fatal cases related to HAV infection in all Brazilian regions 8 have also begun to be noticed.…”
mentioning
confidence: 84%
“…Decrease in HAV circulation 8,9,11,12 as well as a progressive decline in fatal cases related to HAV infection in all Brazilian regions 8 have also begun to be noticed. According to the Brazilian Surveillance System, there is an apparent downward trend in the number of hepatitis A cases reported along the years.…”
mentioning
confidence: 97%
“…All these diagnostic criteria should be present in a patient with an active viral infection to confirm the diagnosis of VAHS 15,17 . Hemophagocytic syndrome associated with hepatitis A virus infection is rarely described, despite the high incidence of this infection in the population in general 4,7,9,32,33,42,47 . There are only 12 cases reported in the medical literature.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, HAV infection accounts for the majority of viral hepatitis notifications 24 . Changes in the epidemiological patterns have been described in some regions due to improvements in sanitation and socioeconomic conditions 10 22 .…”
mentioning
confidence: 99%